Legal and Institutional Framework for Persons With Disabilities in Malaysia - Abdul Wahab, Harlida (The Malaysian Current Law Journal, 2014)
This paper intends to have an overview of the law and institutions that relates to people with disabilities (PWDs) in Malaysia. The issue is basically focussing on the aspect of employment, one of the difficulties faced by PWDs worldwide. Under the legal framework, the discussion is mainly based on the selected provisions in the legislation, namely the Persons With Disabilities Act 2008 (PWDA) which is the cornerstone for the legal recognition to the right of PWDs in Malaysia. As for the institutional framework, the agencies dealing with PWDs are highlighted. It is submitted that legal and institutional framework for PWDs in Malaysia is good enough in acknowledging their rights. Having said this however, few aspects still need to be given attention namely the effective implementation of the law and functioning of the agencies for a better enhancement of PWDs in Malaysia